2017
DOI: 10.1039/c7cc02418e
|View full text |Cite
|
Sign up to set email alerts
|

Ca-NIR: a ratiometric near-infrared calcium probe based on a dihydroxanthene-hemicyanine fluorophore

Abstract: Fluorescent calcium probes are essential tools for studying the fluctuation of calcium ions in cells. Herein, we developed Ca-NIR, the first ratiometric calcium probe emitting in the near infrared region. This probe arose from the fusion of a BAPTA chelator and a dihydroxanthene-hemicyanine fluorophore. It is efficiently excited with common 630-640 nm lasers and displays two distinct emission bands depending on the calcium concentration (K = ∼8 μM). The physicochemical and spectroscopic properties of Ca-NIR al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…Platinum on carbon (Pt/C) is oen used for reduction of nitro to amine in a mild condition without affecting other adjacent groups. [28][29][30] Here, Pt/C was also successfully employed to reduce the nitro group under ambient condition using an H 2 balloon without loss of the benzyl group to produce 12 in excellent yield (Scheme 1, vii).…”
Section: Resultsmentioning
confidence: 99%
“…Platinum on carbon (Pt/C) is oen used for reduction of nitro to amine in a mild condition without affecting other adjacent groups. [28][29][30] Here, Pt/C was also successfully employed to reduce the nitro group under ambient condition using an H 2 balloon without loss of the benzyl group to produce 12 in excellent yield (Scheme 1, vii).…”
Section: Resultsmentioning
confidence: 99%
“…Another NIR probe 13 based on dihydroxanthene-hemicyanine conjugate was developed for the ratiometric detection of Ca 2 + ions ( Figure 6). [37] Compound 13 exhibited emission band at 733 nm andu pon incremental addition of Ca 2 + ions, ad ecreasei nf luorescence intensity at 733 along with an increaseo ff luorescencea t 684 nm occurred. The valueso fd issociation constants correspond to emissions at 684 and 733 were 9.3 AE 0.5 and 7.1 AE 0.2 mm,r espectively.T he pH studies showed that the probe is suitablef or imaging Ca 2 + ions at physiological range (pH 8t o 5).…”
Section: Carboxylate Groups Appended Probesmentioning
confidence: 94%
“…The results revealed that each fluorophore provided fluorescence in their respective channels without any signal intermixing. Another NIR probe 13 based on dihydroxanthene‐ hemicyanine conjugate was developed for the ratiometric detection of Ca 2+ ions (Figure ) . Compound 13 exhibited emission band at 733 nm and upon incremental addition of Ca 2+ ions, a decrease in fluorescence intensity at 733 along with an increase of fluorescence at 684 nm occurred.…”
Section: Carboxylate Groups Appended Probesmentioning
confidence: 99%
“…For example, a way to accelerate the development of NIRs in comparison to more traditionally used synthetic dyes would be to strategically install a built-in, optically tunable group into the traditional NIR fluorescent dye which can enable direct tuning of optical properties. By taking advantage of the optically tunable mechanisms from visible light-emissive dyes, researchers such as Collot et al have created a ratiometric NIR probe [30]. A rational design strategy can facilitate further avenues of functionalization, such as coupling hydrophilic compounds such as dextrans to those calcium sensors [28].…”
Section: Multiplexing Ca 2+ Imaging With Dyesmentioning
confidence: 99%